2021
DOI: 10.3389/frai.2021.636234
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Spatiotemporal Deep Learning Approach for Soil Moisture Prediction and Filling the Gaps in Between Soil Moisture Observations

Abstract: Soil moisture (SM) plays a significant role in determining the probability of flooding in a given area. Currently, SM is most commonly modeled using physically-based numerical hydrologic models. Modeling the natural processes that take place in the soil is difficult and requires assumptions. Besides, hydrologic model runtime is highly impacted by the extent and resolution of the study domain. In this study, we propose a data-driven modeling approach using Deep Learning (DL) models. There are different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, pre‐flood soil moisture also influences flooding. For instance, ElSaadani et al (2021) noted that soil mature determines the likelihood of flooding, while Wasko and Nathan (2019) concluded that changes in soil moisture and rainfall influence flood trend in Australia. Figure 1 depicts the conceptual comparison of the post‐flood results between precipitation‐induced infiltration soil moisture and precipitation plus deep infiltration FRSM on depth for semi‐arid local area south of the Equator.…”
Section: Role Of Rsis For Frsm and Trees In Semi‐arid Floodplainsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pre‐flood soil moisture also influences flooding. For instance, ElSaadani et al (2021) noted that soil mature determines the likelihood of flooding, while Wasko and Nathan (2019) concluded that changes in soil moisture and rainfall influence flood trend in Australia. Figure 1 depicts the conceptual comparison of the post‐flood results between precipitation‐induced infiltration soil moisture and precipitation plus deep infiltration FRSM on depth for semi‐arid local area south of the Equator.…”
Section: Role Of Rsis For Frsm and Trees In Semi‐arid Floodplainsmentioning
confidence: 99%
“…However, preflood soil moisture also influences flooding. For instance,ElSaadani et al (2021) noted that soil mature determines the likelihood of flooding, whileWasko and Nathan (2019) concluded that changes in soil moisture and rainfall influence flood trend in Australia.…”
mentioning
confidence: 99%
“…In addition, a large number of empirical or semi-physical relationships have been developed to link coarse-resolution, satellite-based SM retrievals with other land-surface parameters to obtain finer-resolution and more-continuous SM data products. These fitted models take a wide variety of forms, including optical and thermal temperature/vegetation feature space regression [18][19][20], active and passive microwave data fusion [16,[21][22][23], machine learning [24][25][26], deep learning [27,28], geostatistical methods [29][30][31], and data assimilation methods [32][33][34]. ElSaadani et al investigated the applicability of a convolutional long short-term memory network (ConvLSTM) algorithm for predicting SM and filling observational gaps in south Louisiana in the United States [28].…”
Section: Introductionmentioning
confidence: 99%
“…These fitted models take a wide variety of forms, including optical and thermal temperature/vegetation feature space regression [18][19][20], active and passive microwave data fusion [16,[21][22][23], machine learning [24][25][26], deep learning [27,28], geostatistical methods [29][30][31], and data assimilation methods [32][33][34]. ElSaadani et al investigated the applicability of a convolutional long short-term memory network (ConvLSTM) algorithm for predicting SM and filling observational gaps in south Louisiana in the United States [28]. Prasad et al designed a new multivariate sequential predictive model that utilizes the ensemble empirical mode decomposition (EEMD) algorithm hybridized with extreme learning machines (ELMs) to forecast soil moisture (SM) over weekly horizons [35].…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning (DL) and particularly convolutional neural networks (CNNs) have been exceptionally successful for satellite image analysis tasks including object detection and segmentation. In recent years, DL models have been increasingly used also for modeling continuous spatiotemporal phenomena such as soil moisture (ElSaadani et al, 2021) or air temperature (Amato et al, 2020). Developments in De Bézenac et al (2019) demonstrate that such models can reproduce fundamental physical properties of processes such as advection and diffusion in a purely data-driven way.…”
Section: Introductionmentioning
confidence: 99%